Study on the triaxial compressive properties of alkali activated concrete after freeze-thaw cycles - Yuhua Wang; Mengjun Wang; Congrong Tang; Yong Yu; Shuai Chen (Scientific Reports)
Abstract This study investigates the mechanical behavior of alkali-activated concrete (AAC) subjected to triaxial compression under different confining pressures and freeze-thaw cycles. A series of triaxial compression tests were performed on cylindrical AAC specimens under confining pressures of 0, 3, and 6 MPa, combined with up to 200 freeze-thaw cycles, to evaluate the effects on failure mode, stress-strain response, peak strength, and elastic modulus. The experimental procedure involved specimen preparation, controlled freeze-thaw exposure, and triaxial loading using a servo-controlled testing system. Test results show that increasing confining pressure changes the failure mode from tensile cracking to shear-compression failure, significantly improving load-bearing capacity. Both peak strength and elastic modulus decrease with the number of freeze-thaw cycles, with the most severe degradation observed at 3 MPa, while 6 MPa confining pressure effectively mitigates deterioration. Based on the experimental data, predictive models for the triaxial compressive strength and elastic modulus after freeze-thaw cycles are proposed, and a constitutive model is developed to describe the stress-strain relationship. These findings enhance understanding of AAC durability and provide design references for its application in cold regions and harsh environments.